(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Infertility rate is high globally and in Nigeria. The reported spermicidal activity of Citrus aurantifolia juice (CAJ) and its popular consumption may be a contributing factor to the rise in male infertility. This study examined the effects of CAJ on testis and evaluated the role of calcium and zinc in these effects. Twenty-eight male rats (200-220g) were grouped into four (n=7). Group I (control) received 0.5ml normal saline, while groups II, III and IV received 600mg/kg, 900mg/kg and 1200mg/kg of CAJ, respectively, orally for 35 days. Sperm analysis, testicular histology, testicular zinc and calcium concentrations were evaluated. The results showed a significant decrease (P < 0.001) in body weight and gonad-somatic index (GSI) of the rats in group IV. No sperm cells were found in the sperm samples of all the treatment groups in contrast to control. There was a significant decrease (P < 0.001) in zinc concentration of group III and IV animals and a significant increase (P < 0.001) in testicular calcium content of group III and IV animals. Derangement of testicular cyto-architecture, shrinkage or complete destruction of seminiferous tubules as well as absence of spermatogenic cells were observed in the treatment groups. It was concluded that CAJ induced a destructive effect on testes of rats as evidenced by damaged testicular tissue, reduced gonado-somatic index, azospermia and disruption in testicular electrolyte homeostasis. It was concluded that CAJ caused hypercalcaemia and hypozincaemia in the testicular tissue of the treated rats. Concurrently, CAJ also caused damage to testicular histology, azospermia and decreased GSI. Citrus aurantifolia juice should be consumed with caution due to its potential to cause infertility in males.